1993
DOI: 10.1179/019713693806176490
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging and Solvent Treatments on some Properties of Contemporary Tracing Papers

Abstract: Contemporary tracing papers, also referred to as transparent or translucent paPers, are produced by specially formulated furnish compositions and manufacturing formation processes that can make these papers reactive to solvents used in conservation treatments. An initial study to indicate areas of interest for further work was conducted. Four research projects were designed to determine (1) the various compositions and properties, (2) the degradative effects of aging, (3) some effects of solvents and technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…5), the unprinted samples with a high amount of mineral fillers in their furnish composition (GC, MC, and SC) showed E* values of approximately 7.0, whereas the writing paper (WU), manufactured with bleached hardwood pulp and small amounts of filler, had a E* of 4.2 (difficult to perceive). This E* value was within the reported range by other authors for uncoated paper (Van der Reyden et al 1993;Zappala et al 1996;Bansa and Ishii 1997;Karlovits and Gregor-Svetec 2011).…”
Section: Evaluation Of Color Differencessupporting
confidence: 91%
“…5), the unprinted samples with a high amount of mineral fillers in their furnish composition (GC, MC, and SC) showed E* values of approximately 7.0, whereas the writing paper (WU), manufactured with bleached hardwood pulp and small amounts of filler, had a E* of 4.2 (difficult to perceive). This E* value was within the reported range by other authors for uncoated paper (Van der Reyden et al 1993;Zappala et al 1996;Bansa and Ishii 1997;Karlovits and Gregor-Svetec 2011).…”
Section: Evaluation Of Color Differencessupporting
confidence: 91%
“…It was also clear that the beating technique was used in the manufacture of the plan studied, since the fiber composition is unclear; and this is consistent with the pattern of overbeaten tracing paper, where the pulp is beaten for long period with a high content making the fibers very short and randomly linked. The other techniques dealt with the surface layer of the paper sheet which made the fibrous composition partly clear as mentioned by Der Reyden et al [4]. EDX analysis revealed that the presence of Al, Si, O may be due to the use of kaolinite Al 2 Si 2 O 3 (OH) 4 as a filler in paper manufacture.…”
Section: Discussionmentioning
confidence: 99%
“…The first technique involved submerging paper sheets in materials that have a similar index of refraction as cellulose such as oil, resin, and varnish. The resultant paper is known as vellum paper or impregnated paper as explained by many authors [4][5][6][7][8][9][10]. The second technique involved compressing fiber web of the paper sheet to reduce the air between the paper fibers by submerging paper sheets made from cotton, linen or pure bleached wood pulp in strong acid for seconds to obtain short fibers that are randomly linked.…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose degradation has been the subject of many reports, [53][54][55] with modied papers requiring special attention. 56 Unique aging characteristics may be identied for papers with parchmentized surfaces. Additionally, few studies have focused on photographic papers with such modied surfaces, and it is quite possible that some silver papers that have been assumed to be gelatin without a baryta subbing may in fact be silver prints on parchmentized paper.…”
Section: Discussionmentioning
confidence: 99%